1984
DOI: 10.1145/2080.357392
|View full text |Cite
|
Sign up to set email alerts
|

Implementing remote procedure calls

Abstract: Remote procedure calls (RPC) appear to be a useful paradig m for providing communication across a network between programs written in a high-level language. This paper describes a package providing a remote procedure call facility, the options that face the designer of such a package, and the decisions ~we made. We describe the overall structure of our RPC mechanism, our facilities for binding RPC clients, the transport level communication protocol, and some performance measurements. We include descriptioro~ o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
271
0
6

Year Published

1989
1989
2002
2002

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,306 publications
(277 citation statements)
references
References 5 publications
(1 reference statement)
0
271
0
6
Order By: Relevance
“…Converse supports a message-driven execution model using a construct similar to an RSR, but does not support the concept of a GP. The RSR and GP mechanisms are also related to the remote procedure call (RPC) [5,2]. However, while research has identified RPC as an important structuring principle for clientserver systems, we argue that it is not an appropriate primitive mechanism for parallel computing.…”
Section: Discussionmentioning
confidence: 96%
“…Converse supports a message-driven execution model using a construct similar to an RSR, but does not support the concept of a GP. The RSR and GP mechanisms are also related to the remote procedure call (RPC) [5,2]. However, while research has identified RPC as an important structuring principle for clientserver systems, we argue that it is not an appropriate primitive mechanism for parallel computing.…”
Section: Discussionmentioning
confidence: 96%
“…While the term "service-oriented architecture" is, to our knowledge, a somewhat recent one, related technologies have been the topic of extensive research since at least the early 1970's. One such technology is the remote procedure call (RPC) [BN84], which allows applications to invoke remote functions as if they were local functions. This feature isolates the developer from differences in operating systems, implementation languages, and network protocols used between the various hardware and software components that comprise the application.…”
Section: Related Workmentioning
confidence: 99%
“…The research and use of frameworks can be classified into six distinct generations on the basis of the achieved level of component reuse: (1) Module interconnection languages [4] enabled the reuse of components implemented in a single PL. (2) Remote procedure calls and platform-neutral data representations (e.g., [2,25]) enabled distribution and reuse across PLs. (3) Platform-neutral runtime environments and dynamic component loading (e.g., [7,11]) enabled dynamism and reuse across computing platforms.…”
Section: Related Researchmentioning
confidence: 99%